The road half traveled: agricultural market reform in Sub-Saharan Africa - Kherallah, Mylene; Delgado, Christopher L.; Gabre-Madhin, Eleni Zaude; Minot, Nicholas; Johnson, Michael E. (International Food Policy Research Institute, 2000)
During the past two decades, most countries in Sub-Saharan Africa undertook extensive economic reforms to reduce the role of the government and increase the role of the market in their economies. Because of the importance of the agricultural sector in the region, agricultural market reforms occupied a central place in these liberalization efforts. Agricultural reforms included the removal of price controls, deregulation of agricultural marketing, closure of state-owned enterprises that monopolized agricultural trade, and changes in the foreign exchange market to provide greater incentives for exports. The expectation was that improving price incentives for farmers and reducing government intervention in the agricultural sector would be enough to generate a supply response and allow well-functioning markets to emerge quickly. Almost two decades later, the general consensus is that the reform programs in Sub-Saharan Africa have not met expectations. At the beginning of the 21st century, Sub-Saharan Africa confronts a number of daunting problems: extensive hunger, malnutrition, poverty, resource degradation, and the spread of AIDS. Because the majority of the region’s population remains dependent on agriculture for its livelihood, well-functioning and efficient agricultural markets continue to be key to improving Sub-Saharan Africa’s economic health. This report reviews the extensive evidence on agricultural market reforms in Sub-Saharan Africa and summarizes the impact reforms have had on market performance, agricultural production, use of modern inputs,and poverty. The report offers eight recommmendations for completing the reform process and developing a new agenda for agricultural markets in Sub-Saharan Africa.